The Missing Set: How Landscape Acts in The Cherry Orchard - Ann Leone (Studies in 20th & 21st Century Literature, 2000)
Why is the cherry orchard almost entirely absent from the stage? How does this absent landscape function dramatically? Chekhov's own garden expertise supports a study of the way that landscape in this play—its presence at once pervasive and virtual—both transcends and subverts the functions of setting. Such a reading of the function of landscape leads us to new ways of answering old questions about the play, as well: is the orchard more or other than a symbol? is the play a comedy? I examine the features and conventions of an orchard and garden landscape as they collide with characters' apprehension of the orchard as a repository of the past, and with Lopahin's plans—radical, practical and Romantic—for its future. The orchard's fate parallels the dispersal and re-definition of the family; that shared human and landscape drama can be read to show how landscape is constructed and how that construct depends upon, reflects, and may subvert human intentions.
Keywords: landscape; Chekhov; play; setting; human intentions